Effect of different housing systems (single and group penning) on the health and welfare of commercial female rabbits. (13th June 2020) - Pérez-Fuentes, S.; Muñoz-Silvestre, A.; Moreno-Grua, E.; Martínez-Paredes, E.; Viana, D.; Selva, L.; Villagrá, A.; Sanz-Tejero, C.; Pascual, J. J.; Cervera, C.; Corpa, J. M.
Abstract : In recent decades, concern about rabbit welfare and sustainability has increased. The housing system is a very important factor for animal welfare. However, information about how different available housing types for female rabbits affect their health status is scarce, but this is an important factor for their welfare. Hence, the objective of this study was to evaluate the health status of female rabbits in five common housing systems: three different single-housing systems with distinct available surfaces and heights; a single-housing system with a platform; a collective system. Female rabbits in the collective and platform cages had greater cortisol concentrations in hair than those in the single-housing system with no platform. Haptoglobin concentrations and kit mortality rates during lactation were greater for the collective-cage female rabbits. The collective group had more culled females and more lesions than in the other groups. The main reasons for culling in all the groups were reproduction problems and presence of abscesses, and the collective group of females was the most affected. In conclusion, it appears that keeping females together in collective systems negatively affects their health status and welfare, while single-housing systems imply lower kit mortality rates during lactation and cortisol concentrations, and fewer lesions in female rabbits.